Deep Learning Design in Islamic Boarding School (Pesantren): Integration of Islamic Values, Digital Technology, and 21st-Century Competencies - Ima Hikmayati; Rini Nuraeni; Hernandi Hernandi; Azzahra Anugrah Illahi Sudrajat; Selamet Selamet (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid advancement of digital technology and artificial intelligence has created new opportunities for enhancing learning quality, including within Islamic boarding schools (pesantren). Specific Background: Pesantren, as traditional Islamic institutions, increasingly face the need to integrate modern pedagogical approaches while safeguarding Islamic values. Knowledge Gap: Although research on technology-based education is expanding, studies focusing on the integration of deep learning, Islamic values, and digital technology specifically in pesantren remain limited. Aims: This study aims to conceptualize a deep learning model that harmonizes Islamic teachings, digital tools, and 21st-century competencies to strengthen both academic and character formation in pesantren. Results: Through a literature review, the study identifies three core dimensions of an integrated learning design: Islamic values as the moral-spiritual foundation, digital technology and AI as pedagogical enhancers, and 21st-century skills as essential competencies for santri. Novelty: This study proposes a holistic framework that positions deep learning not only as a cognitive process but as a spiritually grounded, technology-supported educational paradigm unique to pesantren. Implications: Successful implementation requires cultural adaptation, improved digital infrastructure, and continuous teacher training to ensure ethical and effective technology use. Highlights: Integration of Islamic values, digital tools, and deep learning creates a holistic pesantren learning model. Digital technology enhances pedagogy but requires cultural adaptation and teacher training. The framework prepares santri with both spiritual grounding and 21st-century skills. Keywords: Deep Learning, Pesantren, Islamic Values, Digital Technology, 21st-Century Competencies